Brachial pseudoaneurysm associated with median nerve injury as a complication of peripherally inserted central catheter: A case report - Kauffman, Paulo; Helito, Alfredo S; Poltronieri, Mairy JA; Garcia, Marcos R; Viana, Publio CC (Archives of Case Reports, 2019)
Introduction: Peripherally inserted central venous catheters (PICCs) have been increasingly used as an alternative to conventional central venous catheters for long-term administration of chemotherapy, antibiotics, parenteral nutrition, and hydration in patients with difficult venous access. Traumatic complications to arteries and nerves adjacent to veins selected for PICC placement have been rarely described. Case presentation: We report the case of a PICC placement in the brachial vein of the right upper limb of a 78-year-old woman that resulted in brachial artery pseudoaneurysm and median nerve lesion. Discussion: The pseudoaneurysm was successfully repaired with thrombin injection, but neurological deficits to the hand resulting from nerve injury persisted even four months after the procedure.